Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Impact of extrusion-induced protein molecular rearrangement on cooking qualities, in vitro digestibility and gluten allergenicity of durum wheat pasta - Bin Jia; Lavaraj Devkota; Mike Sissons; Edward Attenborough; Dongdong Ni; Sushil Dhital (Food Chemistry, 2025)

Piloting a culturally significant areas framework for spatial planning and management in the coastal environment of South Africa - Loyiso V. Dunga; Kerry J. Sink; Megan G. Van der Bank; Linda R. Harris; Lara Van Niekerk; Myriam Perschke; Ruan Brand; Judy Mann-Lang; Mike Bruton; Mia Strand; Nina Rivers; Stephen Lamberth; et al. (Marine Policy, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

How much deforestation in sub-Saharan Africa has been caused by mining? - Abdulkareem I. Ahmed; Mike R. Massam; Robert G. Bryant; David P. Edwards (Biological Conservation, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Further investigation into the impact of manuring on stable carbon (δ13C) and nitrogen isotope (δ15N) values in pulses: a four-year experiment examining Celtic bean (Vicia faba) - Edward R. Treasure; Darren R. Gröcke; Jonathan J. Lester; Rosie R. Bishop; Samuel E. Jackson; Mike J. Church (Archaeological and Anthropological Sciences, 2024)
Plant stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope values can be used to directly investigate crop husbandry practices such as manuring; a key variable in understanding the scale and intensity of past farming practices. We present new results from a four-year experiment examining the impact of manuring on the δ 13 C and δ 15 N values of a heritage cultivar of the broad or faba bean ( Vicia faba ), the ‘Celtic black broad bean’. This paper builds upon our previous pilot study (Treasure ER, Church MJ, Gröcke DR (2016) The influence of manuring on stable isotopes (δ 13 C and δ 15 N) in Celtic bean ( Vicia faba L.): archaeobotanical and palaeodietary implications. Archaeol Anthropol 8:555–562. https://doi.org/10.1007/s12520-015-0243-6 ). Our results indicate that manuring increased δ 15 N values in beans, with a mean value of 0.5 ± 0.4‰ in control samples compared to a mean value of 2.1 ± 1.3‰ in the most intensively manured plots. It was not always possible to distinguish between an unmanured and manured crop on the basis of δ 15 N values, although manured crops consistently exhibited larger variation in δ 15 N. Bean δ 13 C values show no clear relationship with manuring, although large variability (> 3‰) was found within crops cultivated under the same conditions. Manuring also increased plant biomass production, seed-size and the bean per plant ratio. Overall, we suggest that high δ 15 N values (> 1.5‰) in archaeobotanical remains of pulses can be attributed to small-scale, intensive cultivation that is typical of gardens where manuring rates are very intensive.

Fostering effective and sustainable scientific collaboration and knowledge exchange: a workshop-based approach to establish a national ecological observatory network (NEON) domain-specific user group - Alison Donnelly; Ankur R. Desai; Katherine A. Heckman; Lucas E. Nave; Michael J. Cramer; Marie Faust; Peter Weishampel; Caleb Slemmons; Christian G. Andresen; Edward Ayres; Stacy R. Cotey; Kathryn M. Docherty; et al. (International Journal of Biometeorology, 2024)
The decision to establish a network of researchers centers on identifying shared research goals. Ecologically specific regions, such as the USA’s National Ecological Observatory Network’s (NEON’s) eco-climatic domains, are ideal locations by which to assemble researchers with a diverse range of expertise but focused on the same set of ecological challenges. The recently established Great Lakes User Group (GLUG) is NEON’s first domain specific ensemble of researchers, whose goal is to address scientific and technical issues specific to the Great Lakes Domain 5 (D05) by using NEON data to enable advancement of ecosystem science. Here, we report on GLUG’s kick off workshop, which comprised lightning talks, keynote presentations, breakout brainstorming sessions and field site visits. Together, these activities created an environment to foster and strengthen GLUG and NEON user engagement. The tangible outcomes of the workshop exceeded initial expectations and include plans for (i) two journal articles (in addition to this one), (ii) two potential funding proposals, (iii) an assignable assets request and (iv) development of classroom activities using NEON datasets. The success of this 2.5-day event was due to a combination of factors, including establishment of clear objectives, adopting engaging activities and providing opportunities for active participation and inclusive collaboration with diverse participants. Given the success of this approach we encourage others, wanting to organize similar groups of researchers, to adopt the workshop framework presented here which will strengthen existing collaborations and foster new ones, together with raising greater awareness and promotion of use of NEON datasets. Establishing domain specific user groups will help bridge the scale gap between site level data collection and addressing regional and larger ecological challenges.

Differential advances in budburst timing among black spruce, white spruce and balsam fir across Canada - Diego S. Podadera; Lorena Balducci; Sergio Rossi; Fabrizio Cartenì; Valérie Néron; Rémi Saint-Amant; Stefano Mazzoleni; Jacques Régnière; Eric R.D. Moise; Joseph J. Bowden; Jean-Noël Candau; Alain Dupont; et al. (Agricultural and Forest Meteorology, 2024)

Experimental study on engine and emissions performance of renewable diesel methanol dual fuel (RMDF) combustion - Khanh Duc Cung; Julian Wallace; Vickey Kalaskar; Edward Mike Smith III; Thomas Briggs; Daniel Christopher Bitsis Jr. (Fuel, 2024)

Agrobacterium-mediated transfer of the Fusarium graminearum Tri6 gene into barley using mature seed-derived shoot tips as explants - Dongying Gao; Sidrat Abdullah; Thomas Baldwin; Ann Caspersen; Edward Williams; Alvar Carlson; Mike Petersen; Gongshe Hu; Kathy Esvelt Klos; Phil Bregitzer (Plant Cell Reports, 2024)
Key message We transferred the Tri6 gene into the elite barley GemCraft via new transformation method through shoot organogenesis and identified the rearrangements of transgenes and phenotypic variations in the transgenic plants . Abstract Despite its agronomic and economic importance, barley transformation is still very challenging for many elite varieties. In this study, we used direct shoot organogenesis to transform the elite barley cultivar GemCraft with the RNAi constructs containing Tri6 gene of Fusarium graminearum , which causes fusarium head blight (FHB). We isolated 4432 shoot tips and co-cultured these explants with Agrobacterium tumefaciens . A total of 25 independent T0 transgenic plants were generated including 15 events for which transgene-specific PCR amplicons were observed. To further determine the presence of transgenes, the T1 progenies of all 15 T0 plants were analyzed, and the expected PCR products were obtained in 10 T1 lines. Droplet digital (dd) PCR analysis revealed various copy numbers of transgenes in the transgenic plants. We determined the insertion site of transgenes using long-read sequencing data and observed the rearrangements of transgenes. We found phenotypic variations in both T1 and T2 generation plants. FHB disease was evaluated under growth chamber conditions, but no significant differences in disease severity or deoxynivalenol accumulation were observed between two Tri6 transgenic lines and the wildtype. Our results demonstrate the feasibility of the shoot tip transformation and may open the door for applying this system for genetic improvement and gene function research in other barley genotypes.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

A review of the nature and source of nutrient impairment in small streams: a desk based characterisation for targeted mitigation measures - Sinéad C. Hogan; John J. O’Sullivan; Michael Bruen; Helen P. Jarvie; Edward J. Cox; Mike J. Bowes; Mary Kelly-Quinn (Hydrobiologia, 2023)

Sparing old-growth maximises conservation outcomes within selectively logged Amazonian rainforest - Gianluca Cerullo; Filipe França; Tom Finch; Philip Erm; Hannah Griffiths; Julio Louzada; Chris G. Bousfield; Mike R. Massam; Carlos A. Peres; Jos Barlow; Rhys E. Green; David P. Edwards; et al. (Biological Conservation, 2023)

Agricultural systems regulate plant and insect diversity and induce ecosystem novelty - Jessie Woodbridge; Ralph Fyfe; David Smith; Anne de Varielles; Ruth Pelling; Michael J. Grant; Robert Batchelor; Robert Scaife; James Greig; Petra Dark; Denise Druce; Geoff Garbett; et al. (Anthropocene, 2023)

Climate driven shifts in the synchrony of apple (Malus x domestica Borkh.) flowering and pollinating bee flight phenology - Chris Wyver; Simon G. Potts; Rowan Edwards; Mike Edwards; Deepa Senapathi (Agricultural and Forest Meteorology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

High‐resolution water‐quality and ecosystem‐metabolism modeling in lowland rivers - Devanshi Pathak; Michael Hutchins; Lee E. Brown; Matthew Loewenthal; Peter Scarlett; Linda Armstrong; David Nicholls; Mike Bowes; François Edwards; Gareth Old (Limnology and Oceanography, 2022)
High‐resolution monitoring of water quality and ecosystem functioning over large spatial scales in expansive lowland river catchments is challenging. Therefore, we need modeling tools to predict these processes at locations where observations are absent. Here, we present a new approach to estimate ecosystem metabolism underpinned by a high‐resolution, process‐based model of in‐stream flows and water quality. The model overcomes the current challenges in metabolism modeling by accounting for oxygen transport under varying flows and oxygen transformations due to biogeochemical processes. We implement the model in a 62‐km‐long stretch of the River Thames, England, using observations spanning 2 yr. Model outputs suggest that the river is primarily autotrophic from mid‐spring to mid‐summer due to high biomass during low‐flow periods, and is heterotrophic during the rest of the year. Ecosystem respiration in upstream reaches is driven mainly by biochemical oxygen demand, autotrophic respiration, and nitrification processes, whereas downstream sites also show a control of benthic oxygen demand in addition to the aforementioned processes. Using empirical modeling, we analyze the sensitivity of our estimated metabolism rates to multiple environmental stressors. Results demonstrate that empirical models could be useful for rapid river health assessments, but need improvements to reproduce peak metabolism rates. The process‐based model, although more complex than existing in situ approaches to metabolism quantification, allows inference when gaps in continuous observations are present. The model offers additional benefits for predicting metabolism rates under future scenarios of environmental change incorporating multiple stressor effects.

Induced seismicity due to hydraulic fracturing near Blackpool, UK: source modeling and event detection - Nasim Karamzadeh; Mike Lindner; Benjamin Edwards; Emmanuel Gaucher; Andreas Rietbrock (Journal of Seismology, 2021)
Monitoring small magnitude induced seismicity requires a dense network of seismic stations and high-quality recordings in order to precisely determine events’ hypocentral parameters and mechanisms. However, microseismicity (e.g. swarm activity) can also occur in an area where a dense network is unavailable and recordings are limited to a few seismic stations at the surface. In this case, using advanced event detection techniques such as template matching can help to detect small magnitude shallow seismic events and give insights about the ongoing process at the subsurface giving rise to microseismicity. In this paper, we study shallow microseismic events caused by hydrofracking of the PNR-2 well near Blackpool, UK, in 2019 using recordings of a seismic network which was not designed to detect and locate such small events. By utilizing a sparse network of surface stations, small seismic events are detected using template matching technique. In addition, we apply a full-waveform moment tensor inversion to study the focal mechanisms of larger events ( M L > 1) and used the double-difference location technique for events with high-quality and similar waveforms to obtain accurate relative locations. During the stimulation period, temporal changes in event detection rate were in agreement with injection times. Focal mechanisms of the events with high-quality recordings at multiple stations indicate a strike-slip mechanism, while a cross-section of 34 relocated events matches the dip angle of the active fault.

Bacterial Viruses Subcommittee and Archaeal Viruses Subcommittee of the ICTV: update of taxonomy changes in 2021 - Mart Krupovic; Dann Turner; Vera Morozova; Mike Dyall-Smith; Hanna M. Oksanen; Rob Edwards; Bas E. Dutilh; Susan M. Lehman; Alejandro Reyes; Diana P. Baquero; Matthew B. Sullivan; Jumpei Uchiyama; et al. (Archives of Virology, 2021)
In this article, we – the Bacterial Viruses Subcommittee and the Archaeal Viruses Subcommittee of the International Committee on Taxonomy of Viruses (ICTV) – summarise the results of our activities for the period March 2020 – March 2021. We report the division of the former Bacterial and Archaeal Viruses Subcommittee in two separate Subcommittees, welcome new members, a new Subcommittee Chair and Vice Chair, and give an overview of the new taxa that were proposed in 2020, approved by the Executive Committee and ratified by vote in 2021. In particular, a new realm, three orders, 15 families, 31 subfamilies, 734 genera and 1845 species were newly created or redefined (moved/promoted).

Frequent consumption of sap suggests that omnivory is widespread among Australian geckos - Corrine Edwards; William Cornwell; Mike Letnic (The Science of Nature, 2021)

Sphingosine is able to prevent and eliminate Staphylococcus epidermidis biofilm formation on different orthopedic implant materials in vitro - Sascha Beck; Carolin Sehl; Sylvia Voortmann; Hedda Luise Verhasselt; Michael J. Edwards; Jan Buer; Mike Hasenberg; Erich Gulbins; Katrin Anne Becker (Journal of Molecular Medicine, 2020)
Periprosthetic infection (PPI) is a devastating complication in joint replacement surgery. On the background of an aging population, the number of joint replacements and associated complications is expected to increase. The capability for biofilm formation and the increasing resistance of different microbes to antibiotics have complicated the treatment of PPI, requiring the need for the development of alternative treatment options. The bactericidal effect of the naturally occurring amino alcohol sphingosine has already been reported. In our study, we demonstrate the antimicrobial efficacy of sphingosine on three different strains of biofilm producing Staphylococcus epidermidis , representing one of the most frequent microbes involved in PPI. In an in vitro analysis, sphingosine’s capability for prevention and treatment of biofilm-contamination on different common orthopedic implant surfaces was tested. Coating titanium implant samples with sphingosine not only prevented implant contamination but also revealed a significant reduction of biofilm formation on the implant surfaces by 99.942%. When testing the antimicrobial efficacy of sphingosine on sessile biofilm-grown Staphylococcus epidermidis , sphingosine solution was capable to eliminate 99.999% of the bacteria on the different implant surfaces, i.e., titanium, steel, and polymethylmethacrylate. This study provides evidence on the antimicrobial efficacy of sphingosine for both planktonic and sessile biofilm-grown Staphylococcus epidermidis on contaminated orthopedic implants. Sphingosine may provide an effective and cheap treatment option for prevention and reduction of infections in joint replacement surgery. Key messages • Here we established a novel technology for prevention of implant colonization by sphingosine-coating of orthopedic implant materials. • Sphingosine-coating of orthopedic implants prevented bacterial colonization and significantly reduced biofilm formation on implant surfaces by 99.942%. • Moreover, sphingosine solution was capable to eliminate 99.999% of sessile biofilm-grown Staphylococcus epidermidis on different orthopedic implant surfaces.

Non-alcoholic fatty liver disease and colorectal cancer survival - Kana Wu; Mike Z. Zhai; Erin K. Weltzien; Elizabeth M. Cespedes Feliciano; Jeffrey A. Meyerhardt; Edward Giovannucci; Bette J. Caan (Cancer Causes & Control, 2019)

Acidosis affects muscle contraction by slowing the rates myosin attaches to and detaches from actin - Katelyn Jarvis; Mike Woodward; Edward P. Debold; Sam Walcott (Journal of Muscle Research and Cell Motility, 2018)

Long-term grazing impacts on vegetation diversity, composition, and exotic species presence across an aridity gradient in northern temperate grasslands - Mark P. Lyseng; Edward W. Bork; Daniel B. Hewins; Mike J. Alexander; Cameron N. Carlyle; Scott X. Chang; Walter D. Willms (Plant Ecology, 2018)

Complex problems and unchallenged solutions: Bringing ecosystem governance to the forefront of the UN sustainable development goals - Liette Vasseur; Darwin Horning; Mary Thornbush; Emmanuelle Cohen-Shacham; Angela Andrade; Ed Barrow; Steve R. Edwards; Piet Wit; Mike Jones (Ambio, 2017)

Cattle utilization of coniferous cut blocks under open range grazing and associated impact on tree seedlings - Jillian Kaufmann; Edward W. Bork; Mike J. Alexander; Peter V. Blenis (Agroforestry Systems, 2017)

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Emulator-assisted data assimilation in complex models - Nugzar Yu Margvelashvili; Mike Herzfeld; Farhan Rizwi; Mathieu Mongin; Mark E. Baird; Emlyn Jones; Britta Schaffelke; Edward King; Thomas Schroeder (Ocean Dynamics, 2016)

The influence of manuring on stable isotopes (δ13C and δ15N) in Celtic bean (Vicia faba L.): archaeobotanical and palaeodietary implications - Edward R. Treasure; Mike J. Church; Darren R. Gröcke (Archaeological and Anthropological Sciences, 2016)

Does Increased Road Dust Due to Energy Development Impact Wetlands in the Bakken Region? - Jessica Creuzer; Christina L. M. Hargiss; Jack E. Norland; Thomas DeSutter; Francis X. Casey; Edward S. DeKeyser; Mike Ell (Water, Air, & Soil Pollution, 2016)

Diversity and abundance of solitary and primitively eusocial bees in an urban centre: a case study from Northampton (England) - Muzafar Hussain Sirohi; Janet Jackson; Mike Edwards; Jeff Ollerton (Journal of Insect Conservation, 2015)

Effect of pre-partum feed supplementation on post-partum ovarian activity, milk production and calf growth of small holder dairy Cattle in Cameroon - Pougue Henri Bayemi; Munji Victorine Nsongka; Isabelle Leinyuy; Edward Cottington Webb; Justin Mbanya Nchadji; Daniel Cavestany; Mike Bryant (Tropical Animal Health and Production, 2015)

Tupinambis merianae as nest predators of crocodilians and turtles in Florida, USA - Frank J. Mazzotti; Michelle McEachern; Mike Rochford; Robert N. Reed; Jennifer Ketterlin Eckles; Joy Vinci; Jake Edwards; Joseph Wasilewski (Biological Invasions, 2015)

Multi‐decadal range changes vs. thermal adaptation for north east Atlantic oceanic copepods in the face of climate change - Stephanie L. Hinder; Mike B. Gravenor; Martin Edwards; Clare Ostle; Owen G. Bodger; Patricia L. M. Lee; Antony W. Walne; Graeme C. Hays (Global Change Biology, 2014)
Populations may potentially respond to climate change in various ways including moving to new areas or alternatively staying where they are and adapting as conditions shift. Traditional laboratory and mesocosm experiments last days to weeks and thus only give a limited picture of thermal adaptation, whereas ocean warming occurring over decades allows the potential for selection of new strains better adapted to warmer conditions. Evidence for adaptation in natural systems is equivocal. We used a 50‐year time series comprising of 117 056 samples in the NE Atlantic, to quantify the abundance and distribution of two particularly important and abundant members of the ocean plankton (copepods of the genus Calanus ) that play a key trophic role for fisheries. Abundance of C. finmarchicus , a cold‐water species, and C. helgolandicus , a warm‐water species, were negatively and positively related to sea surface temperature ( SST ) respectively. However, the abundance vs. SST relationships for neither species changed over time in a manner consistent with thermal adaptation. Accompanying the lack of evidence for thermal adaptation there has been an unabated range contraction for C. finmarchicus and range expansion for C. helgolandicus . Our evidence suggests that thermal adaptation has not mitigated the impacts of ocean warming for dramatic range changes of these key species and points to continued dramatic climate induced changes in the biology of the oceans.

The importance of health co-benefits in macroeconomic assessments of UK Greenhouse Gas emission reduction strategies - Henning Tarp Jensen; Marcus R. Keogh-Brown; Richard D. Smith; Zaid Chalabi; Alan D. Dangour; Mike Davies; Phil Edwards; Tara Garnett; Moshe Givoni; Ulla Griffiths; Ian Hamilton; James Jarrett; et al. (Climatic Change, 2013)
We employ a single-country dynamically-recursive Computable General Equilibrium model to make health-focussed macroeconomic assessments of three contingent UK Greenhouse Gas (GHG) mitigation strategies, designed to achieve 2030 emission targets as suggested by the UK Committee on Climate Change. In contrast to previous assessment studies, our main focus is on health co-benefits additional to those from reduced local air pollution. We employ a conservative cost-effectiveness methodology with a zero net cost threshold. Our urban transport strategy (with cleaner vehicles and increased active travel) brings important health co-benefits and is likely to be strongly cost-effective; our food and agriculture strategy (based on abatement technologies and reduction in livestock production) brings worthwhile health co-benefits, but is unlikely to eliminate net costs unless new technological measures are included; our household energy efficiency strategy is likely to breakeven only over the long term after the investment programme has ceased (beyond our 20 year time horizon). We conclude that UK policy makers will, most likely, have to adopt elements which involve initial net societal costs in order to achieve future emission targets and longer-term benefits from GHG reduction. Cost-effectiveness of GHG strategies is likely to require technological mitigation interventions and/or demand-constraining interventions with important health co-benefits and other efficiency-enhancing policies that promote internalization of externalities. Health co-benefits can play a crucial role in bringing down net costs, but our results also suggest the need for adopting holistic assessment methodologies which give proper consideration to welfare-improving health co-benefits with potentially negative economic repercussions (such as increased longevity).

Erratum to: Landscape-Scale Factors Affecting Feral Horse Habitat Use During Summer Within The Rocky Mountain Foothills - Tisa L. Girard; Edward W. Bork; Scott E. Nielsen; Mike J. Alexander (Environmental Management, 2013)

Landscape-Scale Factors Affecting Feral Horse Habitat Use During Summer Within The Rocky Mountain Foothills - Tisa L. Girard; Edward W. Bork; Scott E. Neilsen; Mike J. Alexander (Environmental Management, 2013)

Seasonal diet changes in elephant and impala in mopane woodland - Martine Kos; Arno J. Hoetmer; Yolanda Pretorius; Willem Frederik de Boer; Henjo de Knegt; C. C. Grant; Edward Kohi; Bruce Page; Mike Peel; Rob Slotow; Cornelis van der Waal; Sipke E. van Wieren; et al. (European Journal of Wildlife Research, 2012)

Ecosystem services of wetlands: pathfinder for a new paradigm - Edward Maltby; Mike C. Acreman (Hydrological Sciences Journal, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Large herbivores may alter vegetation structure of semi-arid savannas through soil nutrient mediation - Cornelis van der Waal; Ada Kool; Seline S. Meijer; Edward Kohi; Ignas M. A. Heitkönig; Willem F. de Boer; Frank van Langevelde; Rina C. Grant; Mike J. S. Peel; Rob Slotow; Henrik J. de Knegt; Herbert H. T. Prins; et al. (Oecologia, 2011)

Payments for Ecosystem Services as a Framework for Community‐Based Conservation in Northern Tanzania - FRED NELSON; CHARLES FOLEY; LARA S. FOLEY; ABRAHAM LEPOSO; EDWARD LOURE; DAVID PETERSON; MIKE PETERSON; THAD PETERSON; HASSAN SACHEDINA; ANDREW WILLIAMS (Conservation Biology, 2010)
Payments for ecosystem services (PES) are an increasingly promoted approach to conservation. These approaches seek to develop financial mechanisms that create economic incentives for the maintenance of ecosystems and associated biodiversity by rewarding those who are responsible for provision of ecological services. There are, however, few cases in which such schemes have been used as a strategy for conserving wildlife in developing countries and very few operational examples of such schemes of any sort in sub‐Saharan Africa. In savannah ecosystems, large mammal populations generally depend on seasonal use of extensive areas and are widely declining as a result of habitat loss, overexploitation, and policies that limit local benefits from wildlife. Community‐based conservation strategies seek to create local incentives for conserving wildlife, but often have limited impact as a result of persistent institutional barriers that limit local rights and economic benefits. In northern Tanzania, a consortium of tourism operators is attempting to address these challenges through an agreement with a village that possesses part of a key wildlife dispersal area outside Tarangire National Park. The operators pay the community to enforce voluntary restrictions on agricultural cultivation and permanent settlement in a defined area of land. The initiative represents a potentially cost‐effective framework for community‐based conservation in an ecologically important area and is helping to reconcile historically conflicting local and national interests relative to land tenure, pastoralist livelihoods, and conservation. Wider adaptation of payments for ecosystem services approaches to settings where sustaining wildlife populations depends on local stewardship may help address current challenges facing conservation outside state‐protected areas in savannah ecosystems in sub‐Saharan Africa and other parts of the world.

ORIGINAL ARTICLE: Human impact on an island ecosystem: pollen data from Sandoy, Faroe Islands - Ian T. Lawson; Kevin J. Edwards; Mike J. Church; Anthony J. Newton; Gordon T. Cook; Freddy J. Gathorne‐Hardy; Andrew J. Dugmore (Journal of Biogeography, 2008)
Aim To investigate the form and dynamics of ecosystems on an isolated island in the North Atlantic before human settlement in the first millennium ad , and the effects of human activities thereafter. Location The island of Sandoy, Faroes (61°50′ N, 6°45′ W). Methods Two sequences of lake sediments and one of peat were studied using pollen analysis and sedimentological techniques. Age models were constructed on the basis of radiocarbon dating and, in one case, tephrochronology. The data were analysed statistically and compared with existing data from the region. Results The pollen data indicate that early Holocene vegetation consisted of fell‐field communities probably growing on raw, skeletal soils. These communities gave way to grass‐ and sedge‐dominated communities, which in turn were largely replaced by dwarf shrub‐dominated blanket mire communities well before the first arrival of humans. There is evidence for episodic soil erosion, particularly in the uplands. Changes in the records attributable to human impact are minor in comparison with many other situations in the North Atlantic margins, and with certain published sequences from elsewhere in the Faroes. They include: (1) the appearance of cereal pollen and charcoal, (2) an expansion of ruderal taxa, (3) a decline in certain taxa, notably Juniperus communis and Filipendula ulmaria , and (4) a renewed increase in rates of upland soil erosion. The reliability of palaeoecological inferences drawn from these sites, and more generally from sites in similar unforested situations, is discussed. Main conclusions The subdued amplitude of palynological and sedimentological responses to settlement at these sites can be explained partly in terms of their location and partly in terms of the sensitivity of different parts of the ecosystem to human activities. This study is important in establishing that the imposition of people on the pristine environment of Sandoy, while far from negligible, especially in the immediate vicinity of early farms and at high altitudes, had relatively little ecological impact in many parts of the landscape.

Milk thistle and indinavir: a randomized controlled pharmacokinetics study and meta-analysis - Edward Mills; Kumanan Wilson; Mike Clarke; Brian Foster; Scott Walker; Beth Rachlis; Nick DeGroot; Victor M. Montori; Wayne Gold; Elizabeth Phillips; Stephen Myers; Keith Gallicano (European Journal of Clinical Pharmacology, 2005)

Immunization with a vaccine that combines the expression of MUC1 and B7 co-stimulatory molecules prolongs the survival of mice and delays the appearance of mouse mammary tumors - Vitaly Vasilevko; Anahit Ghochikyan; Nadya Sadzikava; Irina Petrushina; Mike Tran; Edward P. Cohen; Patrick J. Kesslak; David H. Cribbs; Garth L. Nicolson; Michael G. Agadjanyan (Clinical & Experimental Metastasis, 2003)

Book reviews - Mike Gertner; Kirk J. Bundy; Judy L. Cezeaux; Janet C. Rutledge; Edward M. O'Brien (Annals of Biomedical Engineering, 1995)